How do you solve ln(x+1) - lnx = 2? Precalculus Solving Exponential and Logarithmic Equations Logarithmic Models 1 Answer Ahmemaru May 6, 2018 x = 1/(e^2 - 1) Explanation: ln(x+1)-lnx = 2 ln((x+1)/x) = ln(e^2) cancel(ln)((x+1)/x) = cancel(ln)(e^2) (x+1)/x = e^2 x+1 = xe^2 1 = xe^2 - x common factor 1 = x(e^2 - 1) x = 1/(e^2 - 1) Answer link Related questions What is a logarithmic model? How do I use a logarithmic model to solve applications? What is the advantage of a logarithmic model? How does the Richter scale measure magnitude? What is the range of the Richter scale? How do you solve 9^(x-4)=81? How do you solve logx+log(x+15)=2? How do you solve the equation 2 log4(x + 7)-log4(16) = 2? How do you solve 2 log x^4 = 16? How do you solve 2+log_3(2x+5)-log_3x=4? See all questions in Logarithmic Models Impact of this question 2568 views around the world You can reuse this answer Creative Commons License